Monitoring and rendering of visual and photo-biological properties of daylight-redirecting systems. (May 2016) - Borisuit, A.; Kämpf, J.; Münch, M.; Thanachareonkit, A.; Scartezzini, J.-L.
Highlights: Camera-Like Light Sensor (CLLS) investigated distribution of light in V ( λ ) & C ( λ ). We monitored data of two different daylight-redirecting systems by CLLS. We simulated the same two test rooms and compared with our monitoring data. After obtaining comparable results, we made a new comparison in circadian metric. Different daylighting systems, location and time impact non-visual effect of light. Abstract: We previously developed a Camera-Like Light Sensor (CLLS) to record images using a novel High Dynamic Range (HDR) imaging vision sensor. The device was equipped with customized filters for adapting the camera's spectral sensitivity to both photopic and circadian sensitivities. Here, we aim at investigating photometric and circadian metrics to assess and simulate the potential of light on non-visual functions. The CLLS was used to monitor luminance and circadian weighted radiance ( L ec ) over time in two test rooms, equipped with different daylight re-directing devices: venetian blinds (VB) and optical louver systems (OLS). Additionally, a computer simulation was performed for the two test rooms using the software RADIANCE: false colour images were used to demonstrate distribution of luminance and absolute values of L ec . Circadian weighted irradiance ( E ec ) was also computed at different positions corresponding to the gaze directions of a seated office worker. From our results, the VB provided overall higher illuminance compared to the OLS, but when a virtually seated observer was facing desk, the OLS provided larger circadian weighted irradiance in the afternoon. Our results illustrate the use of simulations for circadian metrics, which will be applicable in the future to predict the potential impact of light on non-visual functions for daylighting optimization in buildings.